Ambition of Miguel Rivera in Coco Movie Script - Yusman, Nuuril Abshaari; Moelier, Dahlia D.; Asyrafunnisa, Asyrafunnisa (Fakultas Sastra, Universitas Bosowa, 2025)
This study aimed to find out types of ambition and impacts ambition in the Coco movie script. In this research the writer applied descriptive qualitative method and psychological approach in analysed data through the ambition from of the Alfred Adler and Barsukova theory.The results show that there were three types of ambition used in Coco movie script, there were (1) Ambition on Strive for Success (2) Ambition on Aggressive (3) Ambition on Perfectionist and the impacts ambition there were three impacts ambition based on confidence, ambition based on personal interest , ambition based on strong desire.